2016
DOI: 10.1542/peds.2015-4185
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Tool for Parental Tobacco Treatment in Primary Care

Abstract: We created a clinical decision support (CDS) tool and evaluated its feasibility, acceptability, usability, and clinical impact within the electronic health record to help primary care pediatricians provide smoking cessation treatment to parents/caregivers who smoke. METHODS:This prospective study of pediatric clinicians and parents was conducted at 1 urban primary care site. Clinicians received training in smoking cessation counseling, nicotine replacement therapy (NRT) prescribing, referral to an adult treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Checklists can help the clinician ensure that important topics and points are covered when caring for patients and can also aid in decision‐making. For instance, a clinical decision support tool to help clinicians deliver smoking cessation treatment, which prompts clinicians to ask patients specific questions, has preliminary support for its feasibility and acceptability in clinical care (Jenssen, Bryant‐Stephens, Leone, Grundmeier, & Fiks, ). Furthermore, Recovery Record, a direct‐to‐consumer mobile app that has been downloaded >100,000 times over two years, can be used by individuals with eating disorders to self‐monitor meals, emotions, behaviors, and thoughts and share this information with their therapist (Tregarthen, Lock, & Darcy, ).…”
Section: Addressing Critical Gaps In Treatmentmentioning
confidence: 99%
“…Checklists can help the clinician ensure that important topics and points are covered when caring for patients and can also aid in decision‐making. For instance, a clinical decision support tool to help clinicians deliver smoking cessation treatment, which prompts clinicians to ask patients specific questions, has preliminary support for its feasibility and acceptability in clinical care (Jenssen, Bryant‐Stephens, Leone, Grundmeier, & Fiks, ). Furthermore, Recovery Record, a direct‐to‐consumer mobile app that has been downloaded >100,000 times over two years, can be used by individuals with eating disorders to self‐monitor meals, emotions, behaviors, and thoughts and share this information with their therapist (Tregarthen, Lock, & Darcy, ).…”
Section: Addressing Critical Gaps In Treatmentmentioning
confidence: 99%
“…Clinical reminders and decision support systems within the EHR can also reduce clinician burden in providing TUT. These systems have been implemented in a variety of settings to improve adherence to TUT guidelines and are cost‐effective, sustainable, feasible, and acceptable . Computerized clinical reminders increase the likelihood of documentation, engagement in counseling, and medication prescriptions, and they require minimal training to implement .…”
Section: Resultsmentioning
confidence: 99%
“…Clinical reminders and decision support systems within the EHR can also reduce clinician burden in providing TUT. These systems have been implemented in a variety of settings to improve adherence to TUT guidelines and are cost-effective, sustainable, feasible, and acceptable [42][43][44][45][46]. .…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed that pediatricians found this intervention feasible, acceptable, and usable in promoting smoking cessation (Jenssen BP, 2016). However, this study differed from ours in primary purpose (which was to assess the acceptability, feasibility and usability of the intervention), study design (a prospective study in which all participants received the same treatment) and data collection (assessed via self-reports).…”
Section: Discussionmentioning
confidence: 74%
“…Studies have demonstrated that including relevant prompts in electronic health records (EHRs) can increase smoking cessation promotion in the pediatric clinic (Bunik et al, 2013;Jenssen BP, 2016;Sharifi et al, 2014). To the best of our knowledge, no study has directly compared the effects of a lecture plus EHR prompts, EHR prompts alone, and a lecture alone, on various parameters of smoking cessation promotion.…”
Section: Introductionmentioning
confidence: 99%